What movie will I watch today? The role of online review ratings, reviewers’ comments, and user’s gratification style - Piçarra, N. (2021)
Browsing online ratings and viewers’ comments is an integral part of the experience of choosing and watching a movie. Current theories have broadened the concept of entertainment beyond amusement (hedonic motives) to include experiences of meaning, value, and self-development (eudaimonic motives). With a between-subjects design, we examined the role of the reviewer’s rating (medium rating vs high rating), comments (hedonic vs. eudaimonic), and participant’s gratification style on their interest in watching a movie. Results showed that participants (N = 383) reported a higher preference for the high rating movie. Results also revealed a match between comment type and individual gratification style, with participants with hedonic motives reporting more interest in the movie with hedonic comments, and those reporting eudaimonic motives for the movie with eudaimonic comments.